Exploring Understanding of Islamic Banking Investments: Case Study at Institut Maritim Prasetiya Mandiri - yuliana, yuliana; Milyati, Rina; Ekasariningsih; K. Harahap, Aderina; Vitratin (EAJ (Economic and Accounting Journal), 2025)
The banking industry has advanced significantly, just like conventional banks. The main difference lies in the application of interest rates, where Islamic banks do not implement interest-based systems. The challenge faced is a lack of understanding about Islamic banking investments, which some believe is merely a terminology difference from conventional banks. This research aims to investigate the level of understanding of Islamic banking investments within the Institut Maritim Prasetiya Mandiri. The method employed in this study is qualitative descriptive, using data collection through questionnaires based on a Likert scale. The population consists of faculty members at the Institut Maritim Prasetiya Mandiri. The findings reveal that 18 respondents understand, 22 do not understand, and 20 have no understanding of Islamic banking investments. These result are supported by questionnaire data and analysis using coding and tabulation methods. This study is limited to faculty members at the Institut Maritim Prasetiya Mandiri, and future research should involve a wider sample, including higher education institutions across Lampung and the general public, including business practitioners.